A Model for Predicting Fear of Terrorism through Fear of Crime, Gender, Locus of Control and Coping Strategies - Cohen-Louck, Keren (European journal on criminal policy and research, 2025)
This study examines the assumption that aspects of fear of crime (fear of rape and sense of insecurity) predict fear of terrorism. The online survey included 754 Israeli respondents, who answered questions about their demographic characteristics, fear of terrorism, fear of crime indicators (fear of rape and sense of insecurity), locus of control (LOC; internal and external), and coping strategies. The findings indicate that for women, higher belief in chance and fate, and powerful others (external LOC), higher sense of insecurity, and higher fear of rape were related to a higher fear of terrorism. For men, higher belief in chance and fate (external LOC), higher sense of insecurity, and higher fear of rape were related to a higher fear of terrorism. Furthermore, the effect of fear of rape on fear of terrorism was mediated by sense of insecurity. Our findings support the assumption that fear of crime shadows and affects fear of terrorism for men as well as women. Therefore, fear of rape should be addressed as a significant issue for both genders.